Cobalt‐Copper Nanoparticles Catalyzed Selective Oxidation Reactions: Efficient Catalysis at Room Temperature. Issue 34 (11th September 2018) - Borah, Biraj Jyoti; Mahanta, Abhijit; Mondal, Manoj; Gogoi, Hemen; Yamada, Yusuke; Bharali, Pankaj
Abstract: Bimetallic nanoparticles (NPs) play a pivotal role in promoting high activity and selectivity towards various industrially important reactions in comparison to single metal NPs due to their modulated electronic and surface properties. Herein, we report the synthesis of non‐precious CoCu NPs, which serve as an excellent catalyst for the selective oxidation of a wide range of electronically diverse benzyl alcohols to benzaldehydes, in the presence of tert ‐butyl hydroperoxide (TBHP) as an oxidant at room temperature. The excellent catalytic activity of CoCu NPs is ascribed to a two‐fold synergistic effect arising from the combination of enhanced peroxide decomposition, active Co 2+ catalyst regeneration driven by the faster redox processes (between Co 3+ and Cu + ), and a feasible cobalt dimerisation‐regeneration process. The recoverability and reusability of CoCu NPs are also demonstrated. With the merits of low‐cost and recyclable catalysis under mild conditions, the present catalyst represents an efficient and potential alternative to precious metal catalysts. Abstract : The synthesis of CoCu nanoparticles (NPs) is reported which serve as an excellent catalyst for the selective oxidation of a wide range of electronically diverse benzyl alcohols to benzaldehydes, in the presence of tert ‐butyl hydroperoxide (TBHP) as an oxidant at room temperature. The outstanding catalytic activity of CoCu NPs is ascribed to a two‐fold synergistic effect arising from the combination of enhanced peroxide decomposition, active Co 2+ catalyst regeneration driven by the faster redox processes and a feasible cobalt dimerisation‐regeneration process.